Khảo sát các vùng nguồn sóng thần có khả năng gây nguy hiểm tới vùng bờ biển Việt Nam - Phương, Nguyễn Hồng; Quế, Bùi Công; Xuyên, Nguyễn Đình (Vietnam Journal of Earth Sciences, 2012)
summary Investigation of tsunami sources, capable affecting to the Vietnamese coast Based on the analysis of tectonic feature and geodynamic characteristics of regional faults systems in the South East Asia, nine capable source zones of generating tsunamis that can be affected to the Vietnamese coast were delineated in the East Vietnam Sea and adjacent sea areas. Statistical methods were applied to estimate the seismic hazard parameters for each source zone, which can be used for the detailed tsunami hazard assessment in the future. Maximum earthquake magnitudes are predicted for the Manila Trench (8.3 - 8.7), the Sulu Sea (8.0 - 8.4) and the Selebes Sea source zones (8.1 - 8.5) as well. In the East Vietnam Sea region, the Manila Trench source zone is considered to be the most dangerous to the Vietnamese coast. The estimated Mmax values were used to develop simple scenarios (with a point source assumption) to calculate the tsunami travel time from each source zone to the Vietnamese coast. The results show that for the Manila Trench source zone, tsunamis can hit the Vietnamese coast in two hours at the earliest